Classroom Quality, Classroom Composition, and Age at Entry: Experiences in Early Childhood Education and Care and Single and Dual Language Learners' German Vocabulary - Katharina Kohl; Jessica A. Willard; Alexandru Agache; Lilly-Marlen Bihler; Birgit Leyendecker (SAGE Publishing, 2019)
We examined independent and interactive links among three central characteristics of children's experiences in early childhood education and care and the German receptive vocabulary of single language learners and dual language learners (DLLs). We allowed for possible differential effects depending on children's language background. Our sample included 2,231 children ( n = 1,555 single language learners, n = 371 DLLs from families in which German was frequently spoken, n = 305 DLLs from families in which German was less frequently spoken). Children attended 177 classrooms in 95 early childhood education and care centers and were 30 to 80 months old. We found that classroom process quality predicted German vocabulary only for DLLs with low exposure to German in the family. An earlier age at entry was linked to a larger German vocabulary for all children, but the link was stronger for DLLs from families with low exposure to German. Classroom composition did not predict German vocabulary.